Memahami Disabilitas Intelektual Tokoh Harun: Implementasi Pendidikan Inklusi dalam Novel Laskar Pelangi - Suwarta, Nyoman; Fradana, Ahmad Nurefendi; Gunanjar, Nibras Ali (Universitas 17 Agustus 1945 Surabaya, 2024)
The time and place setting of the novel is Muhammadiyah School in Gantung sub-district on the island of Belitung that has implemented inclusive education in the 1980s, despite the absence of an Inclusive Education Law at the time. This research aims to analyze the portrayal of intellectual disability in the novel Laskar Pelangi, because the theme of intellectual disability of the character in the novel has not been found. Employing a descriptive qualitative method, the study conducts interpretive event analysis, supported by data analysis using theories of educational psychology and social psychology. Eight internal conditions associated with the intellectual disability of the character Harun are identified: 1. Exhibits a humorous demeanor while experiencing intellectual impairment. 2. Belongs to an economically disadvantaged community. 3. Sits quietly and smiles continuously during lessons. 4. Repeats the same questions daily. 5. Recounts identical stories every day. 6. Advances to higher grades despite lacking formal academic records. 7. Maintains a consistent smile during interactions. 8. Displays childlike thinking despite physical maturity. Harun’s cognitive deficits are significant, with an inferred IQ score below 70. The success of special needs education cannot be equated with the academic achievements of typically developing students. Inclusive education’s efficacy hinges on governmental policy support, university collaboration, and familial financial capacity.